Jack Method An Effective Stream Bank Erosion Control Measure - Thampi, C.J. (Journal of Soil and Water Conservation, 2022)
Stream bank erosion is created by unscientific agricultural practices, indiscriminate deforesta-tion, and inattention to the conservation of soil against the ravages of nature. The problem starts from the hills and continues its destructive course not only down to the valley but also along the streams and rivers upto the debris cone into which the entire watershed drains itself. The result is loss of fertile cultivable soil. Most of the streams in Andaman Islands cross through fertile agricultural lands in the valley which are quite narrow and small in extent. The very existence of sound and safe agaiculture is likely to be adversely affected if further extension of the damage due to stream bank erosion is not pre-vented here and now.